The Social Caring Character Development for Students through Youth Red Cross Extracurricular Activities - Rosnelly Rosnelly; Maria Montessori; Junaidi Indrawadi; Yurni Suasti (Fakultas Tarbiyah Institut Agama Islam Sunan Giri Ponorogo, 2023)
The study aims to explain how to develop students' socially caring character through PMR extracurricular activities. This qualitative research uses a case study approach at SMK N 1 Lubuk Sikaping. Social care character development for students is carried out with various activities such as cleaning the school environment, picket guarding the field, assisting victims of natural disasters, and distributing takjil during Ramadan. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis was carried out by data reduction, data presentation, concluding, and verification. The findings of the study concluded that social care Sikaping education for students through PMR co-curricular activities. The results of the study concluded that students' social care character development is aimed at all PMR members, which can be carried out through routine PMR activities, both through material and practice, such as providing assistance to disaster victims, cleaning the school environment, picketing the field, and distributing takjil during the month of Ramadan. This activity impacts the character of being responsive, independent, disciplined, skillful, and irresponsible.